Solitary Fibrous Tumor Arising in the Buccal Space - Tatsuo Okui; Soichiro Ibaragi; Hotaka Kawai; Akira Sasaki (Case Reports in Medicine)
A 39-year-old Japanese woman presented to the Department of Oral and Maxillofacial Surgery, Okayama University Hospital, with the complaint of a slowly growing buccal mass. The mass was well defined, had rounded margins, and was free from skin and muscles. A color Doppler echographic examination indicated high flow velocity of the blood surrounding the mass. Contrast-enhanced images on CT and contrast-enhanced T1-weighted images on MRI displayed a homogeneous enhanced mass with a well-defined margin. A fine-needle aspiration biopsy and histological examination were performed. On immunohistochemistry, spindle cells were strongly positive for CD34, STAT6, and vimentin and negative for EMA, S100, and α-SMA. The tumor was removed with extracapsular dissection. The tumor was composed of bland spindle cells proliferating in a patternless arrangement with a collagenous background. Most of the tumor mass consisted of hypocellular areas including ectatic blood vessels. A prominent branching vascular pattern was observed. Immunohistochemistry demonstrated that the tumor cells were positive for CD34, STAT6, vimentin, and Bcl-2, and negative for α-SMA, S100, and EMA. Three mitotic cells were observed per 10 high-power fields, and the Ki-67 index was 5.7%. The morphological and immunohistochemical features were consistent with a diagnosis of solitary fibrous tumor.